Analisis Sumber Dan Penggunaan Modal Kerja Pada PT. Blue Bird Tbk - Tesalonika M. Supit; Frendy A. O. Pelleng; Joula J. Rogahang (Universitas Sam Ratulangi, 2019)
The purpose of this study was to determine how the implementation of the analysis of sources and uses of working capital at PT. Blue Bird Tbk. The method used is descriptive method using a quantitative approach to the analysis of financial statements. Data and data source is the annual report data from PT. Blue Bird Tbk. The results showed that: (1) Their role of the sources and uses of working capital as a whole, showing the level of effectiveness and efficiency is maintained so the security of the banking financial turnaround can work well and do not affect workers at the PT. Blue Bird Tbk, (2) development of the use of working capital PT. Blue Bird Tbk from years 2016-2017 corresponding financial statement analysis had experienced an increase in which the total assets to net working capital ratio shows the change of + 8,8% ; Current Liabilities to net working capital ratio shows changes + 1% and working capital turnover ratio shows the change of + 6,9%. Observing the development of resources and the use of working capital at PT. Blue Bird Tbk. Shows the rate of change increased (+), then it is suggested, that the company’s ,management constantly review, evaluate and assess reports of capital sources and uses of working capital so that it can ensure the performance of company’s service increasingly better in the future.